Hydrodynamic Effects of River-Lake System Connectivity on Ecological Restoration of Urban Rivers: A Case Study of Liede River - WANG Shaobo; ZHANG Shu; XIONG Yulong; ZHOU Xinmin (Renmin Zhujiang)
To investigate the hydrodynamic effects of river-lake system connectivity on the ecological restoration of urban rivers supplemented by reclaimed water, a four-tier framework was employed to establish a mathematical model of river-lake hydrodynamics and pollutant transport by using the Liede River as an example. The study analyzed the driving response patterns of "system connectivity-regulation and storage-water quality." The findings indicate that the average slope of the Liede River bed is 1.95‰, exhibiting typical characteristics of a mountain stream. The operation of the sluice gate at the mouth of the Liede River primarily affects the water depth of approximately one-third of the river upstream of the gate, while the water depth in the middle and upper reaches is mainly controlled by the upstream replenishment flow. Consequently, when the upstream replenishment flow is constant, changes in the water surface rate and wetted perimeter rate are predominantly concentrated in the downstream one-third of the river. After water system connectivity, the regulation and storage capacity of the artificial lake can sustain the current replenishment flow of the Liede River for approximately 20.1 hours and retain pollutants within the artificial lake for about 3.2 days. Pollutants entering the Liede River take around 10 days to reach the river mouth, effectively mitigating the ecological impact of direct water replenishment from the Changhong Lake Pumping Station. The results demonstrate that optimizing the hydrodynamic conditions of urban rivers supplemented by reclaimed water through water system connectivity can significantly enhance river water quality and aquatic habitat environments, thereby promoting ecological restoration.